Community structure and recruitment of decapods in shallow sub-littoral habitats - Robinson, Martin (Trinity College (Dublin, Ireland). Department of Zoology, 2000)
Although decapod crustaceans represent a major component of benthic fauna in many geographic localities around the world, little is known of their early benthic life history. This study examined the relative influences that larval supply, larval habitat choice and post-settlement processes have in shaping resultant community structure in sub-tidal rocky habitats.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin